2018
DOI: 10.1002/ldr.2898
|View full text |Cite
|
Sign up to set email alerts
|

Object‐oriented soil erosion modelling: A possible paradigm shift from potential to actual risk assessments in agricultural environments

Abstract: Over the last 2 decades, geospatial technologies such as Geographic Information System and spatial interpolation methods have facilitated the development of increasingly accurate spatially explicit assessments of soil erosion. Despite these advances, current modelling approaches rest on (a) an insufficient definition of the proportion of arable land that is exploited for crop production and (b) a neglect of the intra‐annual variability of soil cover conditions in arable land. To overcome these inaccuracies, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 45 publications
2
29
0
1
Order By: Relevance
“…Despite its shortcomings, the USLE and its successor RUSLE (Revised Universal Soil Loss Equation) is still the most common soil erosion model for data scarce catchments. It is reported that at least 90% of soil erosion studies conducted worldwide use RUSLE-based models [18]. According to Wischmeier and Smith, the USLE "is an erosion model designed to compute longtime average soil losses from sheet and rill erosion" [19].…”
Section: Universal Soil Loss Equationmentioning
confidence: 99%
“…Despite its shortcomings, the USLE and its successor RUSLE (Revised Universal Soil Loss Equation) is still the most common soil erosion model for data scarce catchments. It is reported that at least 90% of soil erosion studies conducted worldwide use RUSLE-based models [18]. According to Wischmeier and Smith, the USLE "is an erosion model designed to compute longtime average soil losses from sheet and rill erosion" [19].…”
Section: Universal Soil Loss Equationmentioning
confidence: 99%
“…Particular for spatial resolution, Ding et al [26] reported that spatial resolution beyond 120 m would smother spatial heterogeneity in NDVI calculations. There is also limited information regarding the influence of the interactions of intra-annual variation of different crop cover types in relation to spatial heterogeneity on C value calculations [27].…”
Section: Introductionmentioning
confidence: 99%
“…[28,29]. In the process of quantifying the sensitivity of NDVI-derived C values, finely resolved and temporally dynamic land use information is imperative in order to identify plant cover to specific crop type level and accurately estimate C values for large agricultural landscapes [27]. In addition, topographical variations within a uniform land use type also affect the NDVI-derived C values.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive databases are required to store the information needed to deal with the effects associated with the numerous agricultural practices that exist in the USA and elsewhere. Frequently, in modeling erosion using USLE-based models with Geographic Information Systems in catchments or watersheds, the intra-annual variability of soil cover conditions in arable land is neglected [47].…”
Section: The C Factormentioning
confidence: 99%